Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Alakaram Kila Azkia Garmen Tangerang - Tri Rizkiyani; Rosento Rosento (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
PT Alakaram Kila Azkia Garmen is a company engaged in the textile industry. The company produces various types of clothing. Their products include a variety of T-shirts, pants, and shirts. The company's brand is NUX. This company typically focuses on production quality and design. In carrying out its operations, PT Alakaram Kila Azkia Garmen has many employees who are a driving factor in improving performance quality. This research focuses on determining the extent to which work discipline and the work environment affect employee performance at PT Alakaram Kila Azkia Garmen. The research method used is a quantitative approach with data collection techniques using saturated samples or non-probability sampling, where the entire population is used as a sample. The population in question consists of all employees of PT Alakaram Kila Azkia Garmen, totaling 60 respondents, using questionnaires on a Likert scale. For data processing and analysis, SPSS 25 software is used with multiple linear analysis techniques, including instrument tests, partial and simultaneous hypothesis tests. This study finds that there is a positive and significant influence, both partially and simultaneously, between the variables of work discipline and work environment on employee performance at PT Alakaram Kila Azkia Garmen.